Religious Moderation Campaign Strategy in the Digital Era: Systematic Literature Review (2014-2024) - Muhamad Arif; Moses Adeleke Adeoye; Mohd Kasturi Nor Abd Aziz (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
Religious moderation has become a critical issue globally, particularly in response to the misuse of digital platforms by extremist and intolerant groups to propagate their doctrines. This research seeks to identify the best strategies for conducting religious moderation campaigns and the optimal social media platforms for these efforts in the digital era. Using a systematic literature review methodology, this study focuses on publications from 2014 to 2024, sourced through Publish or Perish, with data from Google Scholar and Scopus databases. The analysis follows the PRISMA framework, emphasizing a rigorous and structured approach to data synthesis. Findings indicate that the CAER strategy Connect Communities, Amplify Positive Messages, Engage Through Technology, and Respect Diversity is highly effective for promoting religious moderation in the digital age. This approach leverages both traditional and digital methods to create impactful campaigns.